The atherogenic effects of chlamydia are dependent on serum cholesterol and specific to Chlamydia pneumoniae - He Hu; Grant N. Pierce; Guangming Zhong (1999)
Epidemiological investigations have linked Chlamydia pneumoniae infection to atherosclerosis. It is not clear, however, whether C. pneumoniae infection plays a causal role in the development of atherosclerosis. Mice with low-density lipoprotein receptor deficiency were induced to develop atherosclerotic lesions in aorta with a cholesterol-enriched diet that increased serum cholesterol by two- to threefold. Using this mouse model, we found that the chlamydial infection alone with either the C. pneumoniae AR39 or the C. trachomatis MoPn strain failed to induce any significant atherosclerotic lesions in aorta over a period of nine months. However, in the presence of a high-cholesterol diet, infection with the C. pneumoniae AR39 strain significantly exacerbated the hypercholesterolemia-induced atherosclerosis, demonstrating that a hypercholesterolemic condition is required for the C. pneumoniae to aggravate the development of atherosclerosis. Although both AR39 and MoPn antigens were detected in aorta of mice infected with the corresponding strains, only mice infected with the C. pneumoniae strain AR39 displayed enhanced atherosclerotic lesions, suggesting that the C. pneumoniae species may possess a unique atherogenic property. This study may provide a model for further understanding the mechanisms of C. pneumoniae atherogenesis and evaluating chlamydial intervention strategies for preventing the advancement of atherosclerotic lesions enhanced by C. pneumoniae infection.